2012
DOI: 10.2139/ssrn.2178911
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Selection with Heterogenous Individuals and Relative Age Effects

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Evans et al (2010) showed that those who are young compared with their peers are more likely to receive a diagnosis of attention deficit hyperactivity disorder.) Additionally to the human capital formation model by Cunha and Heckman (2007), Dawid and Muehlheusser (2012) provided a theoretical foundation to study the channels through which this effect operates. In their model, ability is imperfectly observed and hence partly confounded with maturity (i.e.…”
Section: The Relative Age Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans et al (2010) showed that those who are young compared with their peers are more likely to receive a diagnosis of attention deficit hyperactivity disorder.) Additionally to the human capital formation model by Cunha and Heckman (2007), Dawid and Muehlheusser (2012) provided a theoretical foundation to study the channels through which this effect operates. In their model, ability is imperfectly observed and hence partly confounded with maturity (i.e.…”
Section: The Relative Age Effectmentioning
confidence: 99%
“…In this section we try to address this question empirically. An interesting theoretical contribution is Dawid and Muehlheusser (2012). They theoretically studied optimal selection when individuals differ with respect to (partly unobserved) abilities and relative age, which is partly confounded with ability (assuming that ability and date of birth are uncorrelated).…”
Section: How Are Relative Age and Quality Related?mentioning
confidence: 99%
See 1 more Smart Citation